Campur Kode Bahasa Mahasiswa Universitas Negeri Padang Studi Analisis Terhadap Pelestarian Bahasa - Boty Eryanti; Dila Afrianika; Enjelly Maysi Putri; Jauzaa Syariifah Azzaroh; Juwita Alia; Farel Olva Zulve (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of code-mixing in WhatsApp conversations among Padang State University students, both with fellow students and with lecturers, and its relationship to language preservation. This study used a descriptive qualitative method with data in the form of written utterances in WhatsApp conversations. Data collection was conducted through screenshots and copies of conversations (chats) containing elements of code-mixing. The results of this study indicate that the dominant code-mixing used is external code-mixing in the form of English, such as